Influence of Internal Quality Assurance Practices on Business Education Programme in Colleges of Education in North East Nigeria - Mohammed, , B.; Bappah, , A. S.; Ibrahim, , A.; Inti, , M. M. (Kashere Journal of Education, 2021)
The study investigated the Influence of Internal Assurance Practices on Business Education Programme in Colleges of Education in North East Nigeria. The study has 5 objectives and five null hypotheses. the study adopted descriptive survey design. The study was conducted in six (6) states in North-east, Nigeria. The population of the study was 188 business education lecturers in 9 public Colleges of Education in the study area. Total Population Sample (TPS) was used for the study; hence the entire 188 lectures were used for the data collection. The instrument for the data collection was 4-point rating scale adapted structured questionnaire validated by 5 experts and pilot tested. A reliability of the instrument was determined through pilot study, and Cronbach Alpha was used to determine the reliability of the instrument. A reliability coefficient of .823 was obtained and found to be reliable. The data were collected by the researcher assisted by 6 research assistants. Data collected from the study were analyzed using Statistical Package of Social Science (SPSS, 25) to run mean scores and standard deviations to answer the research questions. Simple Linear Regression was used to test the research hypotheses at 0.05 level of confidence. The study revealed that the Internal Quality Assurance Practice positively influenced curriculum implementation, assessment and evaluation; provisions of facilities and learning resources; students support progression and provision of funds in business education programme in colleges of education in North-east Nigeria. The study concluded that effective internal quality assurance practice helps to improve business education programme Colleges of Education in the study area. Based on this it was recommended among others that, school management and National Commission of Colleges of Education (NCCE) should put in place every mechanism that will enhance quality assurance practices in Business Education programme in North-east, Nigeria.